STRATEGI PENGEMBANGAN TRANSPORTASI WISATA KURA-KURA BUS DI BALI - Kusuma, Ayu; Sasrawan Mananda, IGPB.; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 2 (2017): Jurnal IPTA (Desember 2017)DO - 10.24843/IPTA.2017.v05.i02.p03, 2018)
Kura-Kura Bus is one of tourist transportation companies in Bali with public shuttle bus service in tourism route. Data analysis in this research were using SWOT and AHP analysis, with participants who have position minimal as a supervisor. Participants selected based on their expertise and relevance with this article. Based on the results of SWOT and AHP analysis to develop tourist transportation is Kura-Kura Bus, which is considered the most realistic scenario is an optimistic scenario, with the goal to be a safe and comfortable transportation. To achieve the goal, based on priority strategies that could be done by management of Kura-Kura Bus are developing unique products, finding new markets, favoring public transport services, enchance brand reputation, developing smartphone application, and cross promotion with supplier.